Effectiveness of Career Development Program on Job Satisfaction and Retention of Employees in a Private University in the Philippines. - Nava-Macali, Josephine; Nava-de Jesus, Catherine; Almari, Emma P. (Archives of Business Research, 2019)
The main objective of this descriptive-correlational study was to determine the effectiveness of career development program on employee job satisfaction and retention of 35 non –teaching staff drawn from the different colleges at the University of Perpetual Help System Laguna. The study showed that career coaching and mentoring helps employees to work with others more easily and productively. Guidance and counseling help clarify their goals and how it will contribute to the organization’s overall goals and objectives and that Career Development Program is mainly a function of Human Resources Department. Likewise, Career planning is an integral part of employee training and development and it helps them identify the skills they need to meet future job requirements, and that job rotation improves employees’ planning and organization skills. Furthermore, employees’ training program is aligned with their career development. The study also showed that employees are satisfied with their work because they have the opportunity to learn and grow with the organization, likewise employees are willing to stay with the organization because of good opportunities and career growth. The more effective the perceived effect of the company’s development program the more satisfied they would be in their training and development, the higher the level of satisfaction, the more the employee agree to the factors affecting employee retention and the more effective their company’s career development program the more they agree in career planning and training and development.